Photocatalytic Degradation of Organic Dyes by H4SiW6MoO40/SiO2 Sensitized by H2O2. (26th August 2013) - Yu, Li; Huang, Yongkui; Yang, Yun; Xu, Yulin; Wang, Guohong; Yang, Shuijin
Abstract : H4 SiW6 Mo6 O40 /SiO2 was sensitized by H2 O2 solution that significantly improved its catalytic activity under simulated natural light. Degradation of basic fuchsin was used as a probe reaction to explore the influencing factors on the photodegradation reaction. The results showed that the optimal conditions were as follows: initial concentration of basic fuchsin 8 mg/L, pH 2.5, catalyst dosage 4 g/L, and light irradiation time 4 h. Under these conditions, the degradation rate of basic fuchsin is 98%. The reaction of photocatalysis for basic fuchsin can be expressed as the first-order kinetic model. After being used continuously for four times, the catalyst kept the inherent photocatalytic activity for degradation of dyes. The photodegradation of malachite green, methyl orange, methylene blue, and rhodamine B were also tested, and the degradation rate of dyes can reach 90%–98%.